Phase behavior of poly diacetylene mixed with a xanthene dye at air–water interface and onto solid support. Issue 1 (2nd January 2019) - Suklabaidya, Sudip; Chakraborty, Sekhar; Dey, Bapi; Bhattacharjee, D.; Hussain, Syed Arshad
ABSTRACT: Polydiacetylene (PDA) and its derivatives exhibit interesting photophysical properties, specifically, visible colorimetric transformation which makes them promising candidates for applications in vast number of fields. PDA is obtained through photopolymerization of diacetylene monomers (DA) using UV-irradiation. UV-irradiation leads to the formation of meta stable nonfluorescent blue phase (blue polymer) which on further irradiation converted to stable auto fluorescent red phase (red polymer) with alternating triple and double bonds in ene-yen motif. Herein diacetylene monomers 10, 12-tricosadiynoic acid (TCDA) and amphiphilic octadecyl rhodamine B chloride (RhB18) has been used to prepare mixed Langmuir film. The presence of RhB18 at different molar ratio produces monolayer supramolecular structure as well as typical trilayer structure. Atomic force microscopy investigations gave visual evidence of the formation of trilayer. The mixed film containing TCDA mole fraction≤ 0.8 produces monolayer and TCDA mole fraction≥ 0.85 produces typical trilayer. Photopolymerization is possible only in the trilayer. Thus the phases of PDA can be tuned depending on the molar ratio of TCDA in the mixed film. This study demonstrates that the incorporation of dye RhB18 with diacetylene monomer TCDA provides a means for modulating the structure and chromatic features of PDA assemblies, giving rise to a new morphologies and unique optical properties. This may extend the field of application of PDA assemblies for sensing.